Comparison of gelatin and HES 130/0.4 solution for fluid resuscitation in children with dengue shock syndrome - Merry Mawardi; Tony Rampengan; Jeanette Manoppo; Novie Homenta Rampengan (Paediatrica Indonesiana, 2013)
Background Dengue shock syndrome (DSS) is characterizedby severe vascular leakage and hemostasis disorder, which causesdeath in 1-5% of cases. World Health Organization managementguidelines for fluid resuscitation in DSS remain empirical, ratherthan evidence-based.Objective To as sess the efficacy of ge latin compared tohydroxyethyl starch (HES) 130/0.4 solution for fluid resuscitationin children with DSS.Methods We performed a multi-centered, randomized study tocompare gelatin and HES 130/0.4 solution for resuscitation ofchildren with DSS. We randomly assigned 25 children with DSSto receive gelatin fluid and 25 children to receive HES 130/0.4.Statistical analyses were performed using Chi-square and MannWhitneytests.Results More rapid increase in pulse pressure was noted insubjects treated with HES 130/0.4 compared to those treatedwith gelatin at 8 hours and 28 hours of therapy (P=0.037 andP=0.048). The decrease in hematocrit in subjects treated withHES 130/0.4 was faster than that of gelatin at 4 hours of therapy(P=0.001). One patient died due to an unusual manifestation ofDSS. Respiratory rate decreased faster in subjects treated withHES 130/0.4 than those treated with gelatin at 4 hours and 8hours of therapy (P< 0.05). Body temperature remained higherin subjects treated with gelatin than HES 130/0.4 at 36 hours and48 hours of therapy (P< 0.05). However, the decrease in plateletcounts in subjects treated with HES 130/0.4 was more than thatof gelatin (P=0.018).Conclusion HES 130/0.4 solution may be better for volume replacementcompared to gelatin and is safe for fluid resuscitationin children with DSS.